Agency in health-care: are medical care-givers perfect agents? - Einat Neumann; Shoshana Neuman (Institute for the Study of Labor (IZA), 2007)
It has been suggested in the literature that a source of incompleteness in the agency relationship between the doctor and the patient is that the provider may respond to an incomplete or biased perception of the patient's interests. However, this has not been shown empirically. This paper is novel in presenting an empirical test of the fundamental assumption of the agency model that health care professionals understand what their patients want. Discrete Choice Experiments (DCEs) are conducted simultaneously within samples of patients (women who gave birth) and care-givers (doctors and nurses), to elicit and contrast patients' authentic preferences (for five maternity ward attributes) with what care-givers believe them to be. Conclusion: agents have a biased perception of principals' preferences, and therefore a complete agency relationship does not exist. Our findings add a novel empirical contribution to the agency relationship literature. Moreover, parallel preference patterns of patients and care-givers are certainly of much interest to the field of health economics: Informing the unaware medical care-givers about the patients' preferences, will improve treatment and patients' satisfaction.
urn:nbn:de:101:1-20080402471
Keywords: 330; Pflegeberufe; Patienten; Agency Theory; Diskrete Entscheidung; Präferenztheorie; Test; Israel